An analysis of the post-fault behavior of robotic manipulators - Balakrishnan, Venkataramanan, author; Maciejewski, Anthony A., author; Goel, M., author; IEEE, publisher (Colorado State University. Libraries, 1997)
Operations in hazardous or remote environments are invariably performed by robots. The hostile nature of the environments, however, increase the likelihood of failures for robots used in such applications. The difficulty and delay in the detection and consequent correction of these faults makes the post-fault performance of the robots particularly important. This work investigates the behavior of robots experiencing undetected locked-joint failures in a general class of tasks characterized by point-to-point motion. The robot is considered to have "converged" to a task position and orientation if all its joints come to rest when the end-effector is at that position. It is seen that the post-fault behavior may be classified into three categories: 1) The robot converges to the task position; 2) the robot converges to a position other than the task position; or 3) the robot does not converge, but keeps moving forever. The specific conditions for convergence are identified, and the different behaviors illustrated with examples of simple planar manipulators.
Keywords: position control; velocity control; convergence; redundancy; industrial manipulators; manipulator kinematics; Jacobian matrices